2021
DOI: 10.3390/ijms22189843
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights of Anti-Immune Evasion by Nobiletin through Regulating miR-197/STAT3/PD-L1 Signaling in Non-Small Cell Lung Cancer (NSCLC) Cells

Abstract: Tumor immune escape is a common process in the tumorigenesis of non-small cell lung cancer (NSCLC) cells where programmed death ligand-1 (PD-L1) expression, playing a vital role in immunosuppression activity. Additionally, epidermal growth factor receptor (EGFR) phosphorylation activates Janus kinase-2 (JAK2) and signal transduction, thus activating transcription 3 (STAT3) to results in the regulation of PD-L1 expression. Chemotherapy with commercially available drugs against NSCLC has struggled in the prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“… 64 Nobiletin inhibited PD-L1 expression to reduce anti-immune evasion through the inhibition of the EGFR/JAK2/STAT3 signaling pathway. 65 …”
Section: Discussionmentioning
confidence: 99%
“… 64 Nobiletin inhibited PD-L1 expression to reduce anti-immune evasion through the inhibition of the EGFR/JAK2/STAT3 signaling pathway. 65 …”
Section: Discussionmentioning
confidence: 99%
“…We consider that the development of a PD-L1 inhibitor with marked antioxidant properties can be beneficial. It has been shown that antioxidants can enhance the efficacy of immunotherapy via different mechanisms: (i) via a down-regulation of PD-L1 expression in cancer cells, as observed with the antioxidant natural products such as cardamonin, nobiletin, sesamin and hesperetin [ 40 , 41 , 42 , 43 ], (ii) via an upregulation of major histocompatibility complex and surface activation molecules in dendritic cells, as reported with the antioxidant polysaccharide fucoidan [ 44 ], (iii) via the stimulation of TET2 enzyme leading to an increased intratumoral infiltration of T cells and the expression of cytokines and chemokines, as found recently with the prototypical antioxidant ascorbic acid [ 45 ], or (iv) via other mechanisms implicating the HIF1α/STAT3 pathway for example [ 46 ]. Ascorbic acid (vitamin C) has been shown to empower cancer immunotherapy through its pro-oxidant potential, based on its capacity to modulate epigenetic factors and to regulate expression of different cytokines involved in the immune response [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It effectively inhibits the expression of PD-L1 by targeting the EGFR/JAK2/STAT3 signaling pathway in NSCLC. Nobiletin demonstrates p53-independent suppression of PD-L1 and miR-197 is identified as a regulator of STAT3 and PD-L1 expression [ 233 ].…”
Section: Mirna-mediated Regulation Anti-pd-1 and Anti-pd-l1 Treatment...mentioning
confidence: 99%